Ways To Develop Creative Skills Of Students In Science Education - Saparov Kalandar Abdullayevich; Хasanova Sevara Giyosiddinovna (Global Scientific Publishing, 2024)
In our country, a lot of reforms are being carried out by the educational system management bodies in order to achieve high indicators of educational processes in general education institutions. The formation and development of students as creative individuals depends on the mutual compatibility of changes in their internal and external world, socio-economic conditions, and the implementation of tasks aimed at increasing their creative qualities in educational processes. These practical activities create the need for students to achieve new achievements, move forward to a certain extent, help to develop their learning abilities to some extent. In particular, in the education of natural sciences (SCIENCE), it is possible to achieve a high level of mastery of this science by developing creativity, development of new ideas, and pursuit of innovations
Keywords: educational system; natural science education; creativity